Recent advances in measurement of Pb isotopes in polar ice and snow at sub-picogram per gram concentrations using thermal ionisation mass spectrometry - Vallelonga, Paul; Van de Velde, Katja; Candelone, Jean; Ly, Chi; Rosman, Kevin; Boutron, C. (Elsevier BV, 2002)
Techniques for Pb measurements have reached the stage where Antarctic ice with sub-picogram per gram concentrations can be reliably analysed for isotopic composition. Here, particular attention has been given to measuring the quantity of Pb added during the decontamination and sample storage stages of the sample preparation process because of their impact on accuracy at low concentrations. These stages, including the use of a stainless steel chisel for the decontamination, contributed 5.2 pg to the total sample analysed, amounting to a concentration increase of 13 fg g−1, which is significantly less than expected. Consequently, the corrections to the isotopic ratios and concentration were also smaller. Other contributions to the blank, such as Pb fallout onto critical working areas in the HEPA-filtered air laboratories, were also relatively small as was the amount of Pb leached from preconditioned perfluoroalkoxy (PFA) beakers during sample processing. The ion source contributed typically 89±19 fg to the blank. Although this was relatively large, its influence depended upon the amount of Pb available for analysis and it had the greatest impact when small volumes of samples with a very low concentration were analysed. A 15 months investigation of the leaching characteristics of Pb from a low-density polyethylene (LDPE) sample storage bottle showed 11 fg cm−2 per day was released immediately following the initial 2 months cleaning process, but this decreased to immeasurable values after a further 3 months of cleaning.